PERBANDINGAN PROBLEM BASED CONVENTIONAL LEARNING DENGAN CREATIVE PROBLEM BASED LEARNING TERHADAP SELF REGULATED LEARNING - Fadilah, Ifa Fitriyatul; Prakoso, Albrian Fiky (FKIP Unswagati, 2024)
This study aims to compare between Problem Based Conventional Learning (PBCL) and Creative Problem Based Learning (CPBL) learning models on self-regulated learning in economics. PBCL is a conventional teaching model combined with problem-based learning, which emphasises problem solving with a conventional approach while CPBL is a learning model in which there is an element of creativity that emphasises the use of creativity in solving problems. This research is a type of Quasi Experimental research with Non Equivalent Control Group design. The subjects of this study were students of class XI 5 as the control class and XI 7 as the experimental class at SMA Khadijah Surabaya. The instruments used in this research include economic pre-test post-test questionnaire and self-regulated learning questionnaire. The data in this study was tested using SPSS software. The results showed that there was a significant difference in the economics understanding and SRL skills of students who used the PBCL and CPBL learning models. The experimental class that used CPBL learning model had higher economics understanding and self-regulated learning skills than the control class. This indicates that the CPBL learning model has an influence in improving students' understanding of economic material and students' self-regulated learning skills. Keywords: Creative Problem Based Learning (CPBL), Economics, Experimental, Problem Based Conventional Learning (PBCL), Self Regulated Learning.